Ekosistem Mangrove Binuangeun, Banten: Kondisi Fisik Dan Kimia Serta Ragam Ikan - Fitri Andriyani (Risenologi, 2020)
Binuangeun Mangrove Ecosystem is located in the south western Java Island, in the area of ??Lebak Regency, Banten Province. Mangrove ecosystems are ecosystems that located at the Coastal areas which are a habitat for a variety of marine animals which are associated with it, mostly fish, because of its complex or a very effective root structure which can provide a place for fish to be able to live, take shelter, develop, breed and also look for food. This research was conducted to determine the physical and chemical condition and the variety of fishes which found in the Binuangeu, Banten Mangrove Ecosystem. This research method uses literature study. Physical and chemical conditions of the Binuangeun Mangrove Ecosystem, Banten have degrees of temperature ranging from 28.20 - 32.20; acidity range between 7.00 - 8.09; turbidity ranges from 22.50 - 76.00 NTU; water current ranged from 0.079 to 0.189; phosphate content ranges from 0.02 - 0.008; salinity ranges from 30-35 PSU; and dissolved oxygen content ranges from 5.67 - 8.70. The types of fish found in the Binuangeun Mangrove Ecosystem, Banten are 45 species from 22 Family. The most abundant and relatively high species of existence is the Gobiidae with 10 species. Keywords: Banten, Binuangeun, Ecosystems, Fish, Mangroves